ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK DAN DISPOSISI MATEMATIK SISWA MTs NURUL HATTA KELAS VII PADA MATERI HIMPUNAN - Novi Nurrizbaeni; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
The purpose of this study is to analyze and examine students' communication skills and mathematical dispositions, examine the communication skills in the material set by giving them written tests in the form of essays. The subjects in this study were 10 students of class VIIA MTs Nurul Hatta Ciharasas Bandung Barat. The question instrument used consisted of 5 questions with indicators of mathematical communication skills, and a questionnaire was made to look at mathematical dispositions or students' confidence in mathematics. The research method uses descriptive analysis, which is a case study to determine the extent of achievement of indicators of mathematical communication skills and to know the level of mathematical disposition categories. Processing data is calculated in the form of percent of indicators of cognitive and affective abilities. Based on the results of the highest indicator research that is 100% and the lowest is 20.33%